Understanding the Complexities of Functional Ability in Alzheimer’s Disease: More Than Just Basic and Instrumental Factors - Kahle-Wrobleski, Kristin; Coley, Nicola; Lepage, Benoit; Cantet, Christelle; Vellas, Bruno; Andrieu, Sandrine; PLASA/DSA Group (Current Alzheimer Research, 2014)
Background: Dementia of the Alzheimer’s type (AD) is defined by both cognitive and functional decline; new criteria allow for identification of milder, non-functionally impaired patients. Understanding loss of autonomy in AD is essential, as later stages represent a significant burden and cost to patients, their families, and society. The purpose of the present analyses was to determine the factor structure of the Alzheimer’s Disease Cooperative Study–Activities of Daily Living Scale (ADCS-ADL) in a cohort of AD patients. Methods: Baseline ADCS-ADL assessments of 734 AD patients from the PLASA study were included in an exploratory factor analysis (EFA). Because the ADCS-ADL was designed to assess change over time, change from baseline scores over 2 years were also analyzed using an EFA. Factorial solutions were evaluated based on cross-loading, non-loadings, and number of items per factor. Results: Mean age at baseline was 79.3, mean MMSE was 19.8 and 73.3% of participants were female. Baseline data suggested a 4-factor solution that included factors for basic ADLs (BADLs), domestic/household activities, communication/engagement with the environment, and outside activities. The change scores EFA suggested a 2-factor solution of BADLs and instrumental ADLs (IADLs). Conclusions: Distinct factors of IADLs should be considered for further validation as areas of attention to catch early functional decline.
Keywords: Alzheimer’s